Effect of amylopectin long chains on measured amylose content and their correlation with pasting properties1. Issue 3 (1st November 2012) - Park, Inmyoung; Kim, Seung‐Hyun; Chung, Ill‐Min; Shoemaker, Charles F.
Abstract This paper describes how long chains of AP affect the measurement of AM content and also investigates the rheological properties of purified starches from 14 rice cultivars. The AM content of each rice starch was determined by two different methods: the colorimetric iodine method and the Concanavalin A method. A high‐performance size exclusion chromatograph equipped with multi‐angle laser‐light scattering and RI detectors was used to determine the molecular weight of long chains of AP. Iodine blue values overestimated the AM content because iodine interacts with long chains of AP. However, long chains of AP with molecular weight under 0.89 × 104 g/mol (Calmochi101) did not affect the measurement of AM content by the iodine calorimetric method. Peak temperature correlated positively with AM content and negatively with the number of long chains of AP. Peak viscosity correlated negatively with AM content and molecular weight of long chains of AP. The difference between final viscosity and peak viscosity was larger in long, medium, and short grain rice varieties than in wx grain varieties.